Mutilating predation in the Cheirodontinae Odontostilbe pequira (Characiformes: Characidae) - Lima, Monise R. L.; Bessa, Eduardo [UNESP]; Krinski, Diones; Carvalho, Lucelia Nobre (Soc Brasileira Ictiologia, 2012)
We observed individuals of Odontostilbe pequira, a small characid, approaching and biting individuals of larger-bodied fishes of other species. This observation was made in two clear water headwater streams of the Cuiaba basin, Paraguay River system, located in Nobres, Mato Grosso State, Brazil, which led us to investigate the behavioral interactions of these fish. We characterized behavioral interactions between species by direct underwater observations using snorkelling and video recordings. Additionally, we proceeded diet analyses of O. pequira, obtaining intestinal coefficient and the index of alimentary importance. During underwater observations we checked the relative frequency of attacks by O. pequira on larger fish species. Odontostilbe pequira attacked individually or in large groups, and the anostomid Leporinus friderici was the preferred target prey species, while Prochilodus lineatus was apparently avoided. Our study sustains that O. pequira is omnivorous, with a diet that varies seasonally. It feeds mainly on plants, but also on animal prey, including the scales of small fishes, and, possibly, the mucus and epidermis of larger fish species. We suggest the term "mutilating predation" to describe the latter relationship.

Observamos indivíduos de Odontostilbe pequira, um caracídeo pequeno, abordando e mordendo peixes maiores de outras espécies. Essa observação foi feita em dois riachos de cabeceira com águas cristalinas na bacia do rio Cuiabá, sistema do rio Paraguai, localizados em Nobres, Mato Grosso, Brasil, o que nos levou a investigar a interação comportamental desses peixes. Nós o fizemos através de observações subaquáticas diretas usando mergulho livre e vídeo. Adicionalmente, realizamos a análise da dieta de O. pequira, obtendo seu coeficiente intestinal e índice de importância alimentar. Nas observações subaquáticas avaliamos a frequência relativa dos ataques de O. pequira sobre peixes maiores. Odontostilbe pequira ataca individualmente ou em grupos grandes, o anostomídeo Leporinus friderici foi a presa preferida, enquanto Prochilodus lineatus foi evitado. Este estudo sustenta que O. pequira é um peixe onívoro cuja dieta varia sazonalmente. Ele come principalmente plantas, mas também presas animais, como escamas de peixes pequenos e, possivelmente, muco e epiderme de peixes maiores. Sugerimos o termo “predação mutilante” para descrever essa relação.
Keywords: Animal behavior; Feeding plasticity; Lepidophagy; Underwater observations